2017
DOI: 10.1007/5584_2017_98
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Pharmacology and Roles in Physiology of the P2Y12 Receptor

Abstract: P2Y receptors are G-protein-coupled receptors (GPCRs) for extracellular nucleotides. The platelet ADP-receptor which has been denominated P2Y receptor is an important target in pharmacotherapy. The receptor couples to G mediating an inhibition of cyclic AMP accumulation and additional downstream events including the activation of phosphatidylinositol-3-kinase and Rap1b proteins. The nucleoside analogue ticagrelor and active metabolites of the thienopyridine compounds ticlopidine, clopidogrel and prasugrel bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 169 publications
0
13
0
Order By: Relevance
“…Previous studies with receptor agonists have suggested that activation of both P2Y receptors is required for a full response of platelets to ADP. Generally, the P2Y1 pathway initiates platelet activation and mediates weak responses to ADP, whereas the P2Y12 receptor plays a role in strongly amplifying the platelets activation process and is essential for a full aggregation response to ADP and the stabilization of aggregates [38]. VASP is an intracellular platelet protein that is non-phosphorylated in its basal state.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with receptor agonists have suggested that activation of both P2Y receptors is required for a full response of platelets to ADP. Generally, the P2Y1 pathway initiates platelet activation and mediates weak responses to ADP, whereas the P2Y12 receptor plays a role in strongly amplifying the platelets activation process and is essential for a full aggregation response to ADP and the stabilization of aggregates [38]. VASP is an intracellular platelet protein that is non-phosphorylated in its basal state.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, potent, selective antagonists have only been developed for P2Y 1 (e.g., MRS2179, MRS2279, and MRS2500) and P2Y 12 (e.g., ticagrelor, cangrelor, and clopidogrel) receptors (see Abbracchio et al, ; Kennedy et al, ). These played a major role in identifying physiological roles, such as that of P2Y 1 receptors in peristalsis in the gut (see Kennedy, ) and of P2Y 1 and P2Y 12 receptors in platelet aggregation (Abbracchio et al, ; von Kügelgen, ). Clearly, the development of potent and selective antagonists at the other P2Y subtypes would greatly enhance our ability to determine their functions in health and disease.…”
Section: Introductionmentioning
confidence: 99%
“…played a major role in identifying physiological roles, such as that of P2Y 1 receptors in peristalsis in the gut (see Kennedy, 2015) and of P2Y 1 and P2Y 12 receptors in platelet aggregation (Abbracchio et al, 2006;von Kügelgen, 2017). Clearly, the development of potent and selective antagonists at the other P2Y subtypes would greatly enhance our ability to determine their functions in health and disease.…”
mentioning
confidence: 99%
“…However, P2Y 1 receptors are expressed on various cells in the vascular compartment [49], and, thus, the increased survival could, in principle, result from effects on the endothelial cells or other immune cells. The expression profile for P2Y 12 is (for review, see [50]), however, much more restrictive and is primarily confined to the thrombocytes. Therefore, it is interesting to observe that cangrelor tendentially improve the survival of sepsis even though this is not statistically significant.…”
Section: Discussionmentioning
confidence: 99%